Pengaruh Komunikasi Pimpinan terhadap Kinerja Pegawai Kantor Badan Pemeriksa Keuangan Perwakilan Sumatera Utara - Dina Afifah; Abrar Adhani (UMSU, 2026)
An organization is a place or container for a group of people who work together to achieve a common goal. Each individual in the organization has a specific and complementary role, thus creating harmony in carrying out tasks. Good communication allows the organization to run smoothly and efficiently. Conversely, if communication is lacking or does not work, the organization can experience chaos. Therefore, the role of leadership in organizational communication is very important, because leaders function as one of the main keys to the success of an organization. The purpose of this study is to analyze leadership communication in the North Sumatra Representative Office of the Supreme Audit Agency (BPK), measure employee performance, and identify the influence of leadership communication on that performance. The research method used is a quantitative method that relies on field data collection techniques that focus on numbers and numerical values. The data collection techniques used in this study were questionnaires and documentation. The results of this study indicate that there is a positive and significant influence of leadership communication on employee performance. Leadership communication has an influence on employee performance with an R Square value of 0.788. This indicates a strong and unidirectional relationship. This value indicates that 78.8% of the variation in employee performance is influenced by leadership communication, while 21.2% is influenced by other variables.